Judaism in practice : from the Middle Ages through the early modern period - Fine, Lawrence (Princeton readings in religions., 2001)
This collection of original materials provides a sweeping view of medieval and early modern Jewish ritual and religious practice. Including such diverse texts as ritual manuals, legal codes, mystical books, autobiographical writings, folk literature, and liturgical poetry, it testifies to the enormous variety of practices that characterized Judaism in the twelve hundred years between 600 and 1800 C.E. Its focus on religious practice and experience--how Judaism was actually lived by people from day to day--makes this anthology unique among the few sourcebooks available. The volume encompasses the broad scope and complex texture of Jewish religious practice, taking into account many aspects of Jewish culture that have hitherto been relatively neglected: the religious life of ordinary people, the role and status of women, art and aesthetics, and marginalized as well as remote Jewish communities. It introduces such remarkable personalities as Moses Maimonides, Leon Modena, and Gluckel of Hameln, and presents extraordinary texts on festival practice, Torah study, mystical communities, meditation, exorcism, the practice of charity, and folk rites marking birth and death.